On the “very Brink between Time and Eternity”: Truth, Charity, and Last Dying Speeches in England, c. 1660–1700 - McKenzie, Andrea (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
Late seventeenth-century England witnessed not only the rise of the coffee-house, the newspaper, and party politics, but also a proliferation of printed accounts of treason trials and executions, exposing hearers and readers to opposing religious and political truth claims. Such last dying words, spoken as they were on the “very Brink between Time and Eternity,” were equally compelling and controversial, dividing opinion along partisan and confessional lines. This study builds on recent scholarship emphasizing the dynamism of the Restoration public sphere and the degree to which the gallows was a contested space. It argues that the pamphlet wars over the meaning, veracity, and authenticity of the last dying speeches of late seventeenth-century condemned traitors, while largely overlooked by scholars of the Restoration crisis, have much to tell us about larger, shared preoccupations and mentalities. This article will focus in particular on two powerful contemporary credos which constrained and shaped the actions of authorities, malefactors, and pamphleteers alike: the equation of freedom of speech with liberty and Protestantism on the one hand and the association of charity with the good death, credibility, and truth, on the other.